Seletividade de extratos vegetais utilizados no controle de Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) sobre o predador Marava arachidis (Yersin, 1860) (Dermaptera: Labiidae) - Abreu, Khyson Gomes (2021)
Among the most important pests in maize crops, the fall armyworm Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) stands out. The use of Chemical insecticides is heavily used in their control and, in order to minimize the application of these products, one of the alternatives is plants with bioinsecticide activities, as they are less harmful to humans and the environment. Therefore, it is necessary to search for selective plants to maintain populations of natural enemies in agricultural areas. The species Marava arachidis (Yersin, 1860) (Dermaptera: Labiidae), for example, has a generalist behavior and, as it has a diversified feeding habit, proves to be a predator with great potential to be used in biological control programs. Therefore, considering that the use of plant extracts to control insect pests has become an alternative to chemical insecticides, and the use of extracts on biological control agents is not frequently studied, the objective of this research is to evaluate the selectivity of alcoholic and aqueous plant extracts from different plants with bioinsecticide activity on Marava arachidis (Yersin, 1860). The research was conducted at the Laboratory of Invertebrates (Labin), located in the Department of Biosciences of the Center for Agricultural Sciences, Federal University of Paraíba (CCA-UFPB). To verify the effect of contact and ingestion, plant extracts of: sisal, juazeiro, quince, holy grass, mast, mint, rue, cinnamon, neem and silk flower in concentration were applied and offered to nymphs and adults of M. arachidis 10%. Topically and by ingestion, alcoholic extracts of sisal, juazeiro, quince, holy grass, mast, mint and silk flower are selective, with potential to be used in Integrated Pest Management (MIP) programs, while rue, cinnamon and neem are highly toxic to the predator via topical and ingestion. These plants should be used cautiously when the presence of M. arachidis is verified in the field. By way of topical application and ingestion, aqueous extracts of sisal, juazeiro, quince, holy grass, mast, mint and silk flower are selective for nymphs and adults of Marava arachidis, with the possibility of being used in conjunction with Management programs Integrated Pest (MIP). While rue,cinnamon and neem are harmful to this predator via topical application and ingestion. When in the presence of individuals of M. arachidis in the field, the applications of these plants for the control of S. frugiperda must be carefully considered, as they represent risks to this predator.